Does Increased in Incomes Improves Quality of Life of the Rural Low Income Households? - Hassan, Kalthum; Ahmad, Zalinah; Arshad, Rozita (EconJournals, 2017)
The Malaysian government has implemented various economic development programmes since after the independence. The main goal is to increase the overall populations socio-economic levels which should lead to improved standard of living, well-beings and quality of life. Unfortunately, in most cases quality of life is been misinterpreted and been associated with other concepts such as standard of living and well-being. Hence, it is usually believed that when the standard of living of the low income households is improved, their well-being and the quality of life have also improved. This paper is to explore the indicators of quality of life form the perspective of low income households in rural areas and to analyze the achievement of quality of life among them. It is also determine whether improve in economic achievement promotes improved in quality of life. The findings discover that many low income households who participated in the socio-economic development programmes organized by the development agencies experience increase in income and hence, increase in their standard of living. The low income households have outlined 12 indicators of quality of life. Each household has its own quality of life indicators and all households agree that their quality of life has also improved even though they have not achieved all the outlined indicators. In addition, all respondents agree that improve in household incomes is the main factor to increase in household standard of living, well-being and quality of life